The nexus between foreign direct investment and budget deficit in SADC Region - Hlongwane, Thabang Moses (My University, 2020)
The remarkable increase in FDI flows to developing countries over the last decade has focused attention on whether this source of financing enhances overall development and growth in the economy. To attain foreign direct investment and sustainable economic growth of a country, balanced budget is not only important but necessary. The aim of the study was to examine the nexus between foreign direct investment (FDI) inflows and budget deficit in a panel of five Southern African Development Community (SADC) countries (Malawi, South Africa, Tanzania, Namibia, and Zambia). The study employed the Panel Auto Regressive Distributed Lag (PARDL) model in examining the relationship between budget deficit and FDI. The panel unit root tests results showed different orders of integration (at levels and first-order) giving way to the use of PARDL. Co-integration test results confirmed a long-run relationship in the budget deficit FDI series. In the long run, there is a significant negative relationship between budget deficit and FDI. The speed of adjustment is 36%, implying that the system would converge faster to equilibrium. Furthermore, Granger causality test results indicated a bi-directional causal link on the interest rate – inflation and interest rate – FDI models. However, there is a unidirectional causality running from budget deficit to FDI; interest rate to the budget deficit and FDI to inflation. It is recommended that government should attract more foreign direct investment so as to minimise budget deficit and this could speed up the development of SADC countries. Key Terms: Foreign direct investment, budget deficit, Autoregressive-Distributed Lag, panel data, Granger causality.
Thesis (M.Com. (Economics)) -- University of Limpopo, 2020
Keywords: Foreign direct investment; Budget deficit; Autoregressive-Distributed Lag; Panel data; Granger causality; Investments, Foreign -- Case studies; Economic policy -- Case studie; International business enterprises